Spectroscopic Analyses and the Influence of Concentration on the Photoluminescence Characteristics of Sm+3-Doped Silica Sol-Gel matrix - Salman, Amenah A.; Kadhim, Firas Jawad (Iraqi Journal of Science, 2024)
The sol-gel route is used to prepare samarium (Sm+3) ions doped in silica monoliths as a function of active ion concentrations up to 0.0178%. The spectroscopic activity of Sm+3 ions doped-silica matrices is investigated using UV- Visible spectroscopy and photoluminescence spectroscopy. 4G5/2 emissions are observed from a minority of isolated Sm+3 ions within the pores structure of silica matrix, UV-Vis spectra reveals absorption peaks due to Sm+3 active centers. X-ray diffraction and FTIR results support the distribution of such ions in these porous. Analysis indicates that at high doping levels, most ions reside in clusters and 4G5/2 emission, which is demonstrated by the quenching processes observed in the corresponding spectra. Some spectroscopic parameters such as emission cross-section and oscillator strength are determined and analyzed.